Amplification of hydrological model uncertainties in projected climate simulations of the Upper Indus Basin: Does it matter where the water is coming from?. Issue 10 (26th February 2020) - Dolk, Michaela; Penton, David J.; Ahmad, Mobin D.
Abstract: There is a growing appreciation of the uncertainties in the estimation of snow‐melt and glacier‐melt as a result of climate change in high elevation catchments. Through a detailed examination of three hydrological models in two catchments, and interpretation of results from previous studies, we observed that many variations in estimated streamflow could be explained by the selection of a best parameter set from the possible good model parameters. The importance of understanding changing glacial dynamics is critically important for our study areas in the Upper Indus Basin where Pakistan's policymakers are planning infrastructure to meet the future energy and water needs of hundreds of millions of people downstream. Yet, the effect of climate on glacial runoff and climate on snowmelt runoff is poorly understood. With the HBV model, for example, we estimated glacial melt as between 56% and 89% for the Hunza catchment. When rainfall was a scaled parameter, the models estimated glacial melt as between 20% and 100% of streamflow. These parameter sets produced wildly different projections of future climate for RCP8.5 scenarios in 2046–2075 compared to 1976–2005. Assuming no glacial shrinkage, for one climate projection, we found that the choice among good parameter sets resulted in projected values of future streamflow across a range from +54% to +125%. Parameter selection was the most significant source of uncertainty in the glaciated catchment and amplified climate model uncertainty, whereas climate model choice was more important in the rainfall dominated catchment. Although the study focuses on Pakistan, the overall conclusions are instructive for other similar regions in the world. We suggest that modellers of glaciated catchments should present results from at least the book‐ends: models with low sensitivity to ice‐melt and models with high sensitivity to ice‐melt. This would reduce confusion among decision makers when they are faced with similar contrasting results. Abstract : Climate change studies have estimated different proportions of snow‐melt and glacier‐melt contributions to streamflow. We examine why these estimates of future streamflow have varied using multiple models and parameter sensitivity approaches. We find that parameter uncertainty in glaciated catchments causes significantly different estimates of streamflow response to climate change.